Fast Approximation of Sine and Cosine Hyperbolic Functions for the Calculation of the Transmission Matrix of a Multiconductor Transmission Line - Dikhaminjia, Nana; Rogava, Jemal; Tsiklauri, Mikheil; Zvonkin, Mikhail; Jun Fan; Drewniak, James L. (IEEE transactions on electromagnetic compatibility, 2015)
A fast and stable algorithm for approximation of sine and cosine hyperbolic functions is presented in this paper. The algorithm can be used for S-parameter calculation from RLGC parameters. The idea is to construct the recurrent relation for the approximate solution of sine and cosine hyperbolic complex value matrix functions. The stability of the proposed algorithm is shown and convergence theorem is proved. In the last section, different numerical simulations are made and compared with the already existing algorithm in terms of calculation time given.